Effects of Phoenix dactylifera against Streptozotocin-Aluminium Chloride Induced Alzheimer's Rats and Their In Silico Study. (9th January 2023) - Ismail, Hammad; Khalid, Dania; Ayub, Saad Bin; Ijaz, Muhammad Umar; Akram, Samra; Bhatti, Muhammad Zeeshan; Taqi, Malik Mumtaz; Dilshad, Erum; Anwaar, Sadaf; Batiha, Gaber El-Saber; Aggad, Sarah S.; Yousef, Fatimah M.; et al.
Abstract : Phoenix dactylifera is known for medicinal importance due to its antioxidant, antidiabetic, antidepressant, and anti-inflammatory properties. This study is aimed at evaluating the effect of P. dactylifera seeds to cure Alzheimer's disease (AD). AD was induced in the rats with streptozotocin + aluminium chloride followed by treatment of methanolic extract of P. dactylifera seeds. The blood glucose levels were determined at regular intervals, which showed a prominent decrease in the extracts treated group. Behavior tests, including the Elevated Plus Maze (EPM) test and Morris Water Maze (MWM) test, were used to evaluate memory patterns in rats. The results indicated that extract-treated rats significantly improved memory behavior compared to the diseased group. After dissection, the serum electrolytes, antioxidant enzymes, and choline esterase enzymes were measured in different organs. The serum parameters creatinine, urea, and bilirubin increased after extract treatment. Similarly, the level of antioxidant enzymes like peroxidases (POD), glutathione (GSH), catalase (CAT), superoxide dismutase (SOD), and thiobarbituric acid reactive substance (TBARS) in the extract-treated group showed improved results that were close to the normal control group. The enzyme (lipase, insulin, amylase, and acetylcholine) levels were found enhanced in extract groups as compared to diseased rats. High-performance liquid chromatography (HPLC) was used to determine the level of dopamine and serotonin neurotransmitters, which were increased significantly for P. dactylifera seeds with values of 0.18  μ g/mg tissue and 0.56  μ g/mg tissue, respectively. Overall, results showed that P. dactylifera seeds proved to be quite efficient in improving the memory and behavior of treated rats. The antioxidants and enzymes were also increased; therefore, it may be a potential candidate for treating AD.